MANAGEMENT OF DIGITAL TRANSFORMATION IN THE TEXTILE INDUSTRY - Malikahon A. Kakhkhorova; Yulduz Shakirova Saydalievna (Scholars Digest Publishing, 2024)
This article examines the main aspects of digital transformation management in the textile industry, analyzes forums and seminars aimed at developing the textile industry through digital transformation. The use of Big Data analytics, the Internet of Things, artificial intelligence, robotics and automation of other innovative technologies as ways to digitalize the production of textile products is being studied. The main elements and aspects of digitalization that are used in the textile industry in the implementation of digital solutions are analyzed, and strategies for effective management of digital transformation to achieve successful results are proposed.
Keywords: digitalization, textile industry, automation, Internet of things, artificial intelligence, Big Data.